HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN MOTIVASI LANSIA DALAM PENGONTROLAN HIPERTENSI DI POSYANDU LANSIA KELURAHAN TIPO, SULAWESI TENGAH - Sulfian, Wahyu; Siauta, Viere Allanled; Tumewu, Yohanes (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022, 2022)
Hypertension is a non-communicable disease with increasing age and affects an increasing number of people. Hypertension majority happens to the elderly. The hypertension treatment in the elderly is to control blood pressure, but many elderly neglect it because of the lack of social support from their families. The purpose of this study was to determine the relationship between family social support and the motivation of the elderly in controlling hypertension at the posyandu for the elderly in Tipo Village. The type of research is quantitative using an analytic design with a cross-sectional approach. The number of samples is 30 elderly with used a total sampling design. The analysis data using chi-square test. The results showed that most respondents (86,7%) had good family social support with elderly motivation in controlling hypertension. The results of the bivariate analysis with the chi-square test showed there was a relationship between social support and the motivation of the elderly in controlling hypertension at the posyandu for the elderly in Tipo Village with p-value of 0,001 (p ? 0,05). Conclusions from this study is that family social support is needed by the elderly in motivating the elderly to control their hypertension because a support can increase encouragement for the elderly in carrying out elderly activities so that families are expected to be able to always keep the elderly in control in controlling their hypertension.